2015
DOI: 10.2147/jbm.s78826
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of ASXL1, JAK2V617F mutations and JAK2V617F allele burden in Philadelphia-negative myeloproliferative neoplasms

Abstract: BackgroundDespite insights into the genetic basis of Philadelphia-negative myeloproliferative neoplasms (Ph-negative MPNs), a significant proportion of essential thrombocythemia (ET) and primary myelofibrosis (PMF) patients present with no known MPN disease alleles. There were no previous studies investigating the impact of ASXL1 mutations in Ph-negative MPNs in Turkey. In the current study, we investigated the prognostic significance of ASXL1 mutations in Turkish MPN patients. We also aimed to determine the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…This has recently been reported for PMF, but no significant difference for survival in ET was seen. 13 In addition, mutation in SRSF2 significantly correlated to inferior OS in ET patients in the current study. Three different mutations affecting the mutational hotspot P95 were found in three ET and three PMF patients.…”
supporting
confidence: 52%
“…This has recently been reported for PMF, but no significant difference for survival in ET was seen. 13 In addition, mutation in SRSF2 significantly correlated to inferior OS in ET patients in the current study. Three different mutations affecting the mutational hotspot P95 were found in three ET and three PMF patients.…”
supporting
confidence: 52%
“…In the present study, only one mutation, not previously reported, was found in more than one patient (p.Cys594MetfsX25, found in two cases). Indeed, only 5 of the 11 mutations found in our study have been previously described (Table ) . Other studies have found similar results: of 115 mutations described in the literature , only 21 mutations have been found in more than one case and only 12 have been identified in patients from more than one series.…”
Section: Discussionsupporting
confidence: 87%
“…Although their pathogenetic role in MF remains unclear, ASXL1 mutations have been found early in the course of the disease, suggesting a possible driving role . The most common mutation in MF is p.Gly646TrpfsX12 . The objective of this study was to analyze the frequency, mutational profile and the prognostic significance of ASXL1 mutations in a series of patients with MF diagnosed in eight Spanish hospitals.…”
mentioning
confidence: 99%
“…95 In another experience, ASXL1 mutations (detected in 8.4% of ET patients, and co-existent with JAK2 mutations in two- thirds of them) appeared to confer a statistically insignificant increase in the risk of arterial, but not venous thrombosis. 96 …”
Section: Interactions Between Mutationsmentioning
confidence: 99%